PENGGUNAAN SERBUK GERGAJI DAN AMPAS SAGU DENGAN BEBERAPA KOMPOSISI SEBAGAI MEDIA TUMBUH JAMUR TIRAM PUTIH (Pleurotus ostreatus Jacq.) - Nawaruddin Nawaruddin; Murniati Murniati; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to determine the effect of the composition of sawdust and sago pulp as the best for the growth and development of the oyster mushroom. This research was completely randomize design which the threatments were media composition. K0= 100% sawdust without sago pulp, K1= 75% sawdust without sago pulp, K2= 50% sawdust without sago pulp, K3= 25% sawdust without sago pulp and K4= 0% sawdust without sago pulp. The observed were times a appears mycelium, mycelium growth speed, harvesting age, number of fruit bodies, body weight per baglog fresh fruit, stem length and the biological efficiency. Data were analyzed statistically using analysis of variance. Followed by test of DNMRT 5%. The observation indicated that the use of mixture of sawdust and sago pulp as oyster mushroom growing medium were non significantly in improving mycelium growing speed and efficiency of biology, but tent to be the best of mycelium growing time, amount of fruit and long body stem. Media composition 75% sawdust and 25% sago pulp resulted tent to be best among combination treatments.Key Words: Sawdust, Sago Pulp and Oyster Mushrooms.